NFAT Signaling in Osteoblasts Regulates the Hematopoietic Niche in the Bone Microenvironment - Cheryl L. Sesler; Majd Zayzafoon (Clinical and Developmental Immunology)
Osteoblasts support hematopoietic cell development, including B lymphopoiesis. We have previously shown that the nuclear factor of activated T cells (NFAT) negatively regulates osteoblast differentiation and bone formation. Interestingly, in smooth muscle, NFAT has been shown to regulate the expression of vascular cellular adhesion molecule-1 (VCAM-1), a mediator of cell adhesion and signaling during leukocyte development. To examine whether NFAT signaling in osteoblasts regulates hematopoietic development in vivo, we generated a mouse model expressing dominant-negative NFAT driven by the 2.3 kb fragment of the collagen-αI promoter to disrupt NFAT activity in osteoblasts (dnNFATOB). Bone histomorphometry showed that dnNFATOB mice have significant increases in bone volume (44%) and mineral apposition rate (131%) and decreased trabecular thickness (18%). In the bone microenvironment, dnNFATOB mice displayed a significant increase (87%) in Lineage−cKit+Sca-1+ (LSK) cells and significant decreases in B220+CD19−IgM− pre-pro-B cells (41%) and B220+CD19+IgM+ immature B cells (40%). Concurrent with these findings, LSK cell differentiation into B220+ cells was inhibited when cocultured on differentiated primary osteoblasts harvested from dnNFATOB mice. Gene expression and protein levels of VCAM-1 in osteoblasts decreased in dnNFATOB mice compared to controls. These data suggest that osteoblast-specific NFAT activity mediates early B lymphopoiesis, possibly by regulating VCAM-1 expression on osteoblasts.